1997
DOI: 10.1002/chem.19970030212
|View full text |Cite
|
Sign up to set email alerts
|

The Vinylketene‐Acylallene Rearrangement: Theory and Experiment

Abstract: Alkoxyvinylketenes4are generated by flash vacuum thermolysis (FVT) or photolysis of 3-alkoxycyclobutenones3. The thermal interconversion of4and allene carboxylic acid esters5under FVT conditions is demonstrated by Ar matrix FTIR spectroscopy. In addition, ethoxy-vinylketene4bundergoes thermal elimination of ethene with formation ofs-cis-ands-trans-acetylketene(8). An analogous aminovinylketene-to-allenecarbox-amide conversion is observed on FVT of 3-dimethylaminocyclobutenone3c. A facile 1, 3-chlorine migratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…Interestingly, a search revealed that 1,3-cyclobutanedione existed as its dicyclohexylammonium salt (16). 24 Mono-amination of free 1,3-cyclobutanedione to a cyclobutylenaminone has been described by Wasserman et al 25,26 and we postulated this to be an excellent way to selectively install our single amine moiety. A second step involving the reduction 27 of the enaminone to the aminoalcohol, a reaction not described in the literature so far for a cyclobutylenaminone, was envisaged (Fig.…”
Section: Chemistrymentioning
confidence: 85%
“…Interestingly, a search revealed that 1,3-cyclobutanedione existed as its dicyclohexylammonium salt (16). 24 Mono-amination of free 1,3-cyclobutanedione to a cyclobutylenaminone has been described by Wasserman et al 25,26 and we postulated this to be an excellent way to selectively install our single amine moiety. A second step involving the reduction 27 of the enaminone to the aminoalcohol, a reaction not described in the literature so far for a cyclobutylenaminone, was envisaged (Fig.…”
Section: Chemistrymentioning
confidence: 85%
“…Although to the best of our knowledge there is no precedent in organometallic chemistry for such an isomerization reaction of 12 to 13, an analogous rearrangement has been observed in the thermal interconversion of acylallenes to vinylketenes by flash vacuum thermolysis. [15] Regarding the formation of unsaturated four-membered rings which are connected to an organometallic entity, we note that the groups of Davison, [16] Kolobova, [17] Hughes, [18] and Fischer [19] already reported the synthesis of cyclobutenylidene complexes by [22] cycloaddition of either cationic or neutral vinylidene ± metal precursors and metal alkynyl complexes. However, in this case the generated four-membered ring does not contain an exocyclic CÀC double bond.…”
Section: Dedicated To Professor Heinrich Vahrenkamp On the Occasion Omentioning
confidence: 99%
“…These calculations suggest that the first stable intermediate of the ring-opening of the 3,2-hydrogen shifted cyclic carbene is formyl allene, which subsequently undergoes a 1,4-hydrogen shift and simultaneous C-C s-bond cleavage to yield CO and propyne. However, it is well-known that formyl allene undergoes ready conversion to the more stable vinyl ketene; 41,42 ketenes very readily decarbonylate and the resultant vinyl methylene is likely to suffer the usual 1,2-hydrogen shift to yield the observed allene. The calculated activation energies of potential reaction pathways are summarised in Table 1 and the dominant reaction pathways for both furan itself and the bromofurans are illustrated in Scheme 1.…”
Section: Furan and Bromofuransmentioning
confidence: 99%